ANALYSIS OF COAGULANT NEEDS AND OPERATIONAL COSTS IN THE WATER PURIFICATION PROCESS ON CLARIFIER (Z-9451) IN THE UTILITY UNIT OF PT PERTA ARUN GAS LABORATORY SCALE USING THE JAR TEST METHOD - Mahrizal, M; Elfiana, E; Pardi, P (Politeknik Negeri Lhokseumawe, 2024)
ABSTRACTThis study discusses the analysis of coagulant needs and operational costs in the water purification process on the clarifier (Z-9451) in the utility unit of PT Perta Arun Gas on a laboratory scale using the jar test method. This research is expected to provide benefits in improving the efficiency of chemical use, producing water quality that meets standards and estimating operational costs. This study aims to test the effectiveness of coagulants using jartest on clarifier inlet water samples at PT Perta Arun Gas. The parameters tested include pH, turbidity, and conductivity. Experiments were carried out with variations in the doses of coagulants and polymers. The results of the experiment will be used to determine the optimal dose of coagulant for raw water treatment. The best efficiency In the first week of November 7, 2023, the results of the analysis of the clarifier feed raw water (Z-9451) were obtained, namely a decrease in turbidity of 98.74%. In the second week of November 14, 2023, the decrease in turbidity was 98.42%, in the third week of November 21, 2023, the decrease in turbidity was 98.33%, and in the last week of November 28, 2023, the decrease in turbidity was 98.50%. The results showed the best efficiency in the first week with a concentration of aluminum sulfate of 24 ppm and polymer 0.20 ppm. The use of this concentration is able to produce good water quality and save the company's operational costs. However, weather conditions can affect the quality of raw water, so further research is needed to obtain the optimal conditions for the addition of aluminum sulfate and polymer. It is recommended to conduct a weekly Jartes analysis in order to provide recommendations on the use of aluminum sulfate and polymers as coagulants in utility units. Keywords : Aluminium Sulfat, Clarifier , Jartest, Koagulan, Polymer, Turbidity